Chemical composition and larvicidal activities of Azolla pinnata extracts against Aedes (Diptera: Culicidae) - Rajiv Ravi; Nor Shaida Husna Zulkrnin; Nurul Nadiah Rozhan; Nik Raihan Nik Yusoff; Mohd Sukhairi Mat Rasat; Muhammad Iqbal Ahmad; Intan H. Ishak; Mohamad Faiz Mohd Amin (2018)
The resistance problem of dengue vectors to different classes of insecticides that are used for public health has raised concerns about vector control programmes. Hence, the discovery of alternative compounds that would enhance existing tools is important for overcoming the resistance problem of using insecticides in vectors and ensuring a chemical-free environment. The larvicidal effects of Azolla pinnata extracts by using two different extraction methods with methanol solvent against Aedes in early 4th instar larvae was conducted.